Comparison of Hand-Sewn versus Coupled Venous Anastomoses in Traumatic Lower Extremity Reconstruction - Stranix, John T.; Rifkin, William J.; Lee, Z-Hye; Anzai, Lavinia; Jacoby, Adam; Ceradini, Daniel J.; Thanik, Vishal; Saadeh, Pierre B.; Levine, Jamie P. (Journal of Reconstructive Microsurgery, 2019)
Background Microvascular reconstruction of the lower extremity has the highest reported complication and flap failure rates of any anatomical region. Despite widespread adoption of the mechanical anastomotic venous coupler and encouraging results in other anatomical regions, there are limited reports examining its use in the lower extremity. This study compares outcomes between coupled and hand-sewn venous anastomoses in traumatic lower extremity reconstruction.Methods Retrospective review of our institutional flap registry from 1979 to 2016 identified soft tissue free flaps performed for the reconstruction of Gustilo type IIIB/IIIC open tibial fractures. Patient demographics, flap characteristics, use of a venous anastomotic coupler, and perioperative outcomes were examined. Analysis was performed using chi-square and Student's t-tests.Results A total of 361 patients received a microvascular free flap for coverage of a Gustilo type IIIB or IIIC tibial fracture following traumatic injury. After excluding cases that lacked adequate information on coupler use, 358 free flaps were included in the study. There were 72 (20%) free flaps performed using a venous coupler and 286 (80%) performed with hand-sewn venous anastomoses. There were comparable rates of major complications (22.2 vs. 26.1%; p = 0.522), total flap failure (6.5%, vs. 10.2%; p = 0.362), and partial flap failure (9.7 vs. 12.2%; p = 0.579) between venous coupler and hand-sewn anastomoses, respectively. Furthermore, use of the venous coupler was not associated with increased rates of operative take backs (22.8 vs. 23.0%; p = 0.974). However, reconstructions performed using a venous coupler were significantly more likely to have a second venous anastomosis performed (37.5 vs. 21.3%; p = 0.004).Conclusion Complication and flap failure rates were similar between reconstructions performed with a venous coupler and those performed with hand-sewn venous anastomoses. These findings suggest that use of the venous anastomotic coupler is safe and effective in lower extremity reconstruction, with comparable outcomes to conventional sutured anastomoses.
Keywords: venous coupler; lower extremity; microvascular anastomosis